As territorialidades que emergem na gestão das águas: um caminho para a Agenda 21 - Pereira, Luiz Firmino Martins (2009)
The present work looked for to apprehend the territorialities that are appearing in the water management process, raised for the current Water Resources National Policy, contrasting the possibilities of these territorialities, with the classic context of absence of effective processes to transpose obstacles that has been observed in the growth of the cities, which usually result in the territorial arranges. The social relationships gave resultants that were apprehended, and were confronted to the beginnings of the Agenda 21, which represents an instrument for a new model of development. Aiming at the new water resource legislation, it was looked for the results of a practical case, the one of the participatory management in the Lakes Region - RJ, the appearance of new territorialities, your subjective relationships and the movements of the social groups that integrates it. Its organization and results were researched, indicating a new dimension that is shown opportune for new sources of power through new territorialities. As the experiences of participatory watershed management were very newest in the country, and the application of the instruments foreseen in Water Resource Law incites to emerge territorialities, the study concludes that these management processes can be an excellent way for the implantation of a regional Agenda 21, and also propose an action platform where the watershed management inserts and stirs up the consolidation of Agenda 21.